Introduction in culture in vitro of Deschampsia аntarctica Desv. (Poaceae) from two regions of Maritime Antarctica - O. M. Zahrychuk; N. M. Drobyk; I. A. Kozeretska; I. Yu. Parnikoza; V. A. Kunakh (Ukrainian Antarctic Journal, 2012)
There were developed conditions for seeds germination, micropropagation as well as for induction of callus formation from root and stem explants for a long-term Deschampsia antarctica Desv. tissue culture growing. Optimal for micropropagation of the species was nutrient medium B5 with 0,2 mg/l Kin; for callusogenesis of both explants types – the same medium supplemented with 0,9 mg/l 2,4-D and 0,09 mg/l BAP. Callusogenesis from the root explants considerably exceeded (2-2,6 times) that from the stem one.